Pengaruh Peningkatan Harga Jual Kopra Untuk Menutupi Modal Usaha - Rahma Dunggio; Yuli afriati; Susyulan Sarapil (Agricultural Socio-Economic Empowerment and Agribusiness Journal, 2024)
Coconut is one of the agricultural commodities that plays an important role in the economy of Gorontalo Province, especially as a source of income for farmers. However, the increasing production costs of coconut, especially copra, are significant challenges. This article analyzes the costs, revenues, and income of copra businesses. The research method is quantitative descriptive analysis. Data were collected based on interviews with farmers and direct observations in the field. The results of the study showed that the average cost of copra business is IDR 5,299,610 / production, with the largest cost component being the cost of coconut climbing labor, the value of copra business revenue of IDR 8,805,384 / production, and income of IDR 3,505,774 / production.